Monday

April 21, 2014

April 21, 2014

Posted by **Allison** on Saturday, March 12, 2011 at 8:14pm.

- Calculus -
**bobpursley**, Saturday, March 12, 2011 at 8:28pmdy/dx=2(t-3)dt/dx

but

dx/dt=e^t, so

dy/dx=2(t-3)e^-t

so m= that. Now when x=1, (x=e^t), t must be zero, so

m=2(-3)=-6

y=-6x+b

now, at point 1,9

9=-6+b,or b=15, so equation for line must be

y=-6x+15

check that.

- Calculus -
**Allison**, Saturday, March 12, 2011 at 8:46pmI just figured it out! thank you!

**Related Questions**

Calculus - If f(x)=(3x)/(1+x^2) find f′(4). Use this to find the equation ...

Calculus - Find the equation of the tangent line to the curve y=2sinx at the ...

calculus - -find the equation of the tangent line to the curve y=5xcosx at the ...

math calculus - Use implicit differentiation to find the equation of the tangent...

Calculus - Please help this is due tomorrow and I dont know how to Ive missed a ...

calculus - If f(x)=4x^(5/2), find f'(4) Use this to find the equation of the ...

Calculus - Find an equation of the tangent line to the curve at the given point...

Calculus. I need help! - HARDER PARTS WAS 3(x^2+y^2)^2=26(y^2+y^2) Find the ...

COLLEGE CALCULUS. - Use implicit differentiation to find the equation of the ...

calculus - Find the equation of the tangent line to the curve y=sqrt(x) at x = c...